2019
DOI: 10.1002/acr.23717
|View full text |Cite
|
Sign up to set email alerts
|

Substituting Sedentary Time With Physical Activity in Fibromyalgia and the Association With Quality of Life and Impact of the Disease: The al‐Ándalus Project

Abstract: In regression models, allocating time of sedentary behavior to either LPA or MVPA was associated with better quality of life and lower disease impact in women with fibromyalgia. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 49 publications
0
18
0
3
Order By: Relevance
“…The effect size (partial eta squared) was reported for each statistical test [41]. In accordance with Cohen [42], effect sizes were classified as small (0.01 ≤ η 2 < 0.06), medium (0.06 ≤ η 2 < 0.14), or large (η 2 ≥ 0.14). A listwise deletion method was applied for intention-to-treat analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The effect size (partial eta squared) was reported for each statistical test [41]. In accordance with Cohen [42], effect sizes were classified as small (0.01 ≤ η 2 < 0.06), medium (0.06 ≤ η 2 < 0.14), or large (η 2 ≥ 0.14). A listwise deletion method was applied for intention-to-treat analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, sedentary time is independently and positively associated with levels of pain, fatigue, and impact of the disease in women with FM . When sedentary time is substituted with light PA, better bodily pain, social function, vitality, and disease impact are observed …”
Section: Introductionmentioning
confidence: 99%
“…21 When sedentary time is substituted with light PA, better bodily pain, social function, vitality, and disease impact are observed. 22 Few studies have examined the follow-up of the interventions of physical exercise in FM; Moreover, the long-term effects PA programs remain unknown. A prospective longitudinal study with 70 female FM patients showed a significant improvement in FM status after 3 years.…”
mentioning
confidence: 99%
“…14 Among the factors that could positively influence fibromyalgia symptoms, there is evidence that higher levels of physical activity of different intensities and lower levels of sedentary behaviour are associated with better symptomatology. [15][16][17] Unfortunately, the difficulties when coordinating productive and reproductive work could lead to a lack of time for these women, 7 which is a potential barrier to participating in physical activity. 18 This potential relationship between work type and physical activity, which may determine health in this group of patients, is, however, not well characterised as yet.…”
Section: Introductionmentioning
confidence: 99%